Diagnosis of Histomonas meleagridis in naturally infected turkeys in different areas of Tikrit and Hawija District, Iraq (Tikrit Journal of Veterinary Science, 2024)
Clinical signs are Depression, loss of appetite, body weight loss with yellow foul smell diarrhea in some cases, as well as head drooping and ruffled feathers and the cyanosis head was observed only in a few cases of  Poult. Macroscopic examination of cecum and liver samples showed an increase in thickness of cecum walls, in addition to the presence of bleeding and hard cheesy materials in the cecal cavity, while in the liver there was an enlargement and necrotic foci of different sizes and shapes.